Knowledge, attitudes and practices on nutrition labels of Registered Nutritionist-Dietitians from Laguna, Philippines - Principe, Meyrick T.; Villarino, Casiana Blanca J. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
This cross-sectional, non-experimental study aimed to describe the knowledge, attitudes, and practices (KAPs) of 61 actively practicing Registered Nutritionist-Dietitians (RNDs) from Laguna, Philippines towards nutrition labels. In addition, it examined the association of the RNDs KAP with their characteristics - length of practice, field of practice, and geographical location. The KAPs were measured using a content-validated questionnaire. All the RNDs came from a first class province of diverse geographical classification. Descriptive statistics and frequency distributions were used to analyze the responses on KAPs. Themes were formulated based on open-ended responses related to self-reported practice. Pearsons r and factor analysis were used to identify factors that determine the RNDS KAP and association of knowledge, attitudes and practices towards nutrition labels, respectively. Chi-square test determined the association of KAP with the RNDs characteristics. Results showed that RNDs from Laguna have low knowledge on nutrition labels (67.68%). They were more familiar with nutrition label interpretation (78.69%) and government regulations (61.75%) of nutrition labels, while there was less familiarity on usefulness (58.47%), nutrition and health claims (53.30 %), and truthfulness (44.81%) of nutrition labels. Factors that comprise attitudes on nutrition labels were: 1) interpretation; 2) nutrition and health claims; 3) usefulness; and 4) government regulation. The RNDs had unfavorable reaction towards accuracy and truthfulness of nutrition labels, nutrition and health claims, and front of label dietary guideline. The factors that influenced their practices were: 1) explanation of nutrition and health claims; 2) discussion of usefulness to patients; and 3) explanation to ix patients on the use of terms on nutrition labels. Key information on nutrition label such as % DV and % RENI, nutrient claims, per 100g column and fat information were not always discussed among their patients despite being RNDs. Positive attitude on nutrition labels of RNDs was directly related to knowledge of nutrition and health claims, usefulness, and government regulation. Those with favorable attitude on interpretation also explained nutrition and health claims of labels to their patients or community. Respondents with favorable attitude on usefulness of nutrition labels also discussed usefulness of nutrition labels to patients. Only 43% responded always when asked if they personally read nutrition labels. RNDs in this study do not personally check % RENI, % DV, and front of label Guideline Daily Amounts (GDA) as frequently as expected despite having the assumed expertise in nutrition and health. However, if they do personally check, it is driven mainly by health reasons. There was no significant association between the KAPs of the RNDs with their length of practice, field of practice, and geographical location. The study identifies suggestions for improvement on nutrition label education, policy support and training of RNDs to effectively achieve an attitude shift towards appreciation of nutrition labels which may help their patients or the community have informed food choice.
Thesis (Master of Science in Nutrition)--University of the Philippines Diliman.
Keywords: Nutritionists -- Philippines -- Laguna; Nutrition extension work -- Philippines -- Laguna; Food -- Labeling -- Philippines